ADVANTAGES AND DISADVANTAGES OF ELIMINATING THE OBLIGATION TO PUBLISH SCIENTIFIC JOURNALS FOR POSTGRADUATE STUDENTS IN COMPLETING THEIR FINAL ASSIGNMENTS - Maryam Salampessy; Zulham; Monika Sutarsa; Andika Isma; Akbar (CV. ADIBA AISHA AMIRA, 2023)
Based on the results of the SWOT analysis in descriptive form and the table above, it can be concluded that the policy of eliminating the publication of scientific articles for master's, applied master's, doctoral and applied doctoral students has more weaknesses and threats than strengths and opportunities, as the researcher explains and explains in on. Therefore, researchers conclude that this policy is not yet mature and should not be implemented now. The KEMENDIKBUDRISDIKTI should conduct a comprehensive study and research first by listening to the groups involved, such as students and lecturers